Constraints in adoption and strategies to promote polyhouse technology among farmers: A multi-stakeholder and multi-dimensional study - PRABHAKAR, ITIGI; VIJAYARAGAVAN, K; SINGH, PREMLATA; SINGH, BALRAJ; JANAKIRAM, JANAKIRAM; MANJUNATHA, B L; JAGGI, SEEMA; SEKAR, I (The Indian Journal of Agricultural Sciences, 2017)
The study was conducted on 120 farmers and 30 agricultural researchers each of two states, viz. Maharashtra and Karnataka to delineate the constraints in adoption of polyhouse. The farmers faced environmental, technical, labour, economic and marketing constraints in harnessing profitability and sustainability of this technology. The major constraints in rapid adoption were high initial investment, poor availability of quality planting material and inputs, poor post-harvest infrastructure and absence of price policy measures. Farmers of Maharashtra were found to be better placed with respect to market access and availability of quality planting material. All the stakeholders agreed that R&D initiatives were required to develop low cost designs and reduce the cost of cultivation under polyhouse. Farmers' ability to successfully integrate this technology to suit their socio-economic and agro-ecological conditions would further affect its profitability and sustainability.